Corneal endothelial dysfunction: etiology, pathogenesis, and current treatment approaches - S.V. Trufanov; E.P. Salovarova (РМЖ "Клиническая офтальмология")
The article reviews current approaches to the treatment of corneal endothelium dysfunction. The most common causes of endothelial decompensation are Fuchs’ corneal dystrophy and secondary bullous keratopathy. Bullous keratopathy is characterized by progressive corneal edema and occurs mainly in elderly population. The major goals of the treatment are to minimize persistent corneal edema and to improve associated discomfort and poor vision. At early stages, medical treatment may provide short-term symptomatic effect but does not result in the recovery thus delaying visual rehabilitation. Keratoplasty is an effective, pathogenically-based treatment for these disorders. Previously, penetrating keratoplasty has been the gold standard surgical procedure for corneal endothelial failure. Currently, modified techniques of endothelial keratoplasty (i.e., DSAEK, DMEK) are the first-line surgery for these disorders. Replacing only diseased corneal layers has several advantages, i.e., preserving of corneal architectonics, rapid visual recovery, surgery through the corneal tunnel incision, no need to use expensive equipment. Ongoing studies are to assess the efficacy of isolated descemetorhexis and transplantation of cultivated endothelial cells as well as to discover substances which stimulate corneal endothelial regeneration.  Keywords: cornea, endothelium, corneal dystrophy, keratopathy, endothelial keratoplasty, DSAEK, DMEK, DMET, descemetorhexis.  For citation: Trufanov S.V., Salovarova E.P. Corneal endothelial dysfunction: etiology, pathogenesis, and current treatment approaches. Russian Journal of Clinical Ophthalmology. 2019;19(2):116–119.  About the authors: Sergey V. Trufanov — MD, PhD, Leading Researcher, ORCID iD 0000-0003-4360-793Х; Elena P. Salovarova — postgraduate, ORCID iD 0000-0002-0624-8379. Scientific Research Institute of Eye Diseases. 11а, Rossolimo str., Moscow, 119021, Russian Federation. Contact information: Elena P. Salovarova, e-mail: sep1991@inbox.ru. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 19.06.2018.